Sistem Informasi Penyewaan Barang Elektronik pada CV. Mundi Mulya Pratama - Abu Tholib; Moch Subchan Mauluddin (Universitas Wahid Hasyim, 2023)
The growth of today's technology is developing very fast, most people cannot be separated from the internet world. This has a positive impact on getting updated information in this final project, the author tries to take advantage of this opportunity to create a web-based information system. This system is the stage in system development that is not too complicated starting from the analysis and definition of system requirements that will be made after that the design and implementation stages of system integration and testing after that the system maintenance stage the results obtained by the author can create an electronic goods rental information system that can carry out goods rental transactions in the form of 5 units of laptops and 4 units of printers and it is also hoped that the Goods Rental Information System can facilitate matters of leasing goods by ordering goods via online without coming to the company.